Oxidative stress and DNA lesions: the role of 8-oxoguanine lesions in Trypanosoma cruzi cell viability. - Pedro H N Aguiar (Public Library of Science (PLoS), 2013)
The main consequence of oxidative stress is the formation of DNA lesions, which can result in genomic instability and lead to cell death. Guanine is the base that is most susceptible to oxidation, due to its low redox potential, and 8-oxoguanine (8-oxoG) is the most common lesion. These characteristics make 8-oxoG a good cellular biomarker to indicate the extent of oxidative stress. If not repaired, 8-oxoG can pair with adenine and cause a G:C to T:A transversion. When 8-oxoG is inserted during DNA replication, it could generate double-strand breaks, which makes this lesion particularly deleterious. Trypanosoma cruzi needs to address various oxidative stress situations, such as the mammalian intracellular environment and the triatomine insect gut where it replicates. We focused on the MutT enzyme, which is responsible for removing 8-oxoG from the nucleotide pool. To investigate the importance of 8-oxoG during parasite infection of mammalian cells, we characterized the MutT gene in T. cruzi (TcMTH) and generated T. cruzi parasites heterologously expressing Escherichia coli MutT or overexpressing the TcMTH enzyme. In the epimastigote form, the recombinant and wild-type parasites displayed similar growth in normal conditions, but the MutT-expressing cells were more resistant to hydrogen peroxide treatment. The recombinant parasite also displayed significantly increased growth after 48 hours of infection in fibroblasts and macrophages when compared to wild-type cells, as well as increased parasitemia in Swiss mice. In addition, we demonstrated, using western blotting experiments, that MutT heterologous expression can influence the parasite antioxidant enzyme protein levels. These results indicate the importance of the 8-oxoG repair system for cell viability.